2023
DOI: 10.3389/fenvs.2023.1085936
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability reports: Differences between developing and developed countries

Abstract: Achieving sustainability is a major challenge faced by many societies. The increasing moral consciousness of stakeholders has put pressure on companies, forcing these companies to include long-term policies that reflect the regionally specific needs of stakeholders. Using a structural topic model, this study identified differences between developing and developed countries with respect to sustainability disclosures. Data were obtained from 2100 sustainability reports published in the United Nations Global Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 112 publications
0
0
0
Order By: Relevance
“…However, it is noteworthy that developed countries have placed too much emphasis on the role of technological innovation in innovation development and pollution reduction, while neglecting the importance of social and policy innovation (Barykin et al, 2022). Moreover, developed countries have tended to rely too heavily on market mechanisms and have lacked government and social involvement in pollution control (Kvasničková Stanislavská et al, 2023). Studies have found that the dominant role of governments in environmental governance is more pronounced in developing countries than in developed ones, and this government-led environmental governance model can better guarantee the implementation of environmental policies, resulting in more effective improvement of environmental quality (Spilker, 2012;.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is noteworthy that developed countries have placed too much emphasis on the role of technological innovation in innovation development and pollution reduction, while neglecting the importance of social and policy innovation (Barykin et al, 2022). Moreover, developed countries have tended to rely too heavily on market mechanisms and have lacked government and social involvement in pollution control (Kvasničková Stanislavská et al, 2023). Studies have found that the dominant role of governments in environmental governance is more pronounced in developing countries than in developed ones, and this government-led environmental governance model can better guarantee the implementation of environmental policies, resulting in more effective improvement of environmental quality (Spilker, 2012;.…”
Section: Introductionmentioning
confidence: 99%